Mid Term Appraisal Ninth Five Year Plan 1997-2002 Rajasthan - Planning Commission (Planning Commission, 1997)
The State of Rajasthan has 32 administrative districts, 100 Sub-divisions, 229 Tehsils and 237 development blocks. With 3.42 lakh sq. kms. of area, Rajasthan is the second largest State in the country, accounting for over 10 per cent of the total geographical area. The state has a population of 4.40 crores (census 1991), about 77 per cent of it living in rural areas. The population of scheduled castes and scheduled tribes is 17.29 per cent and 12.44 per cent respectively of the State's total population.
Government of Rajasthan, Planning Department